Prospek Keberlanjutan Wisata Energi Terbarukan Di Pantai Baru, Kabupaten Bantul - Puspita Sari, Dian Dwi; Setiawan, Bakti (Jurnal Ilmiah Pariwisata; Vol 24 No 1 (2019): Jurnal Ilmiah PariwisataDO - 10.30647/jip.v24i1.1241, 2019)
T ourism conditions for renewable energy in the new coastal tourism area so far have not maximally attracted tourists and the region has not supported tourism activities. This can be seen from the imbalance in the increase of coastal tourists with renewable energy, which should get attention because it is a benchmark of the mismatch between demand and the availability or availability of existing fields. This study aims to determine the handling of tourism areas for renewable energy that are in accordance with the wishes of tourists, with the aim of tourism studies, supply-demand, and drawing conclusions and recommendations for handling tourism. The approach uses the Quantitative - Two Steps Questionnare method, with the research instrument in the form of a questionnaire through two stages. The result is a discrepancy between supply and demand for infrastructure. Then it needs to be improved so that the tourist area continues.There is a demand for 6 amenities (gates, parking lots, toilets, lodgings, restaurants, souvenir shops) and the development of promotional information by managers within the coastal area through social media. Assessment of supply-demand, namely medium-importance (attractions, accessibility, promotional information), medium-is very important for amentias. The average value is the condition of moderate supply, meaning that it needs improvement because demand says the availability of the field is important to continue the potential of renewable energy as a tourist attraction. Environmental aspects that are very influential in sustainability, if the environment is good then the socio-culture improves and the economy increases.